2006
DOI: 10.1002/per.557
|View full text |Cite
|
Sign up to set email alerts
|

Beyond resilients, undercontrollers, and overcontrollers? an extension of personality prototype research

Abstract: Prototypes of personality were investigated in two studies. In study I, clusters of Big‐Five‐based prototypes were examined using a general population sample of 1908 German adults. Convergent evidence suggested the appropriateness of a five‐cluster solution, which corresponds to previously identified temperament based prototypes. In study II, the five‐cluster solution was cross‐validated in a sample of 256 prisoners. Moreover, it was shown that a population‐based approach (using discriminant functions derived … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
153
3
22

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(188 citation statements)
references
References 43 publications
10
153
3
22
Order By: Relevance
“…In this paper, we examined the connections between personality and unemployment by using the Big Five personality traits as such. According to Herzberg and Roth (2006), numerous studies have proposed three major personality prototypes that configure the Big Five personality traits within an individual: 1) Resilients (low score in neuroticism, high or intermediate scores in other traits), 2) Overcontrolled (high neuroticism, low extraversion), and 3) Undercontrolled (low scores in conscientiousness and neuroticism). Using the same JYLS data as in the present study, Kinnunen et al (in press) also identified the three groups of personality (resilients, overcontrolled, and undercontrolled) with slightly different configurations.…”
Section: Discussionmentioning
confidence: 99%
“…In this paper, we examined the connections between personality and unemployment by using the Big Five personality traits as such. According to Herzberg and Roth (2006), numerous studies have proposed three major personality prototypes that configure the Big Five personality traits within an individual: 1) Resilients (low score in neuroticism, high or intermediate scores in other traits), 2) Overcontrolled (high neuroticism, low extraversion), and 3) Undercontrolled (low scores in conscientiousness and neuroticism). Using the same JYLS data as in the present study, Kinnunen et al (in press) also identified the three groups of personality (resilients, overcontrolled, and undercontrolled) with slightly different configurations.…”
Section: Discussionmentioning
confidence: 99%
“…Although it would have been interesting to investigate adolescents who judged their personality types differently over the waves as well, 2 we 1 During the review process of this paper, Asendorpf (2006) and Herzberg and Roth (2006) published a paper in which they suggested other initial cluster centres. They suggest that the initial cluster centres for resilients should be set at 0.5 for extraversion, conscientiousness and emotional stability and 0.25 for agreeableness and openness.…”
Section: Personalitymentioning
confidence: 99%
“…For the multi-group analyses we compared 3 We reran both models with five longitudinal personality groups (N ¼ 568). According to Caspi and Silva (1995) and Herzberg and Roth (2006), two additional personality types may be present, namely a reserved personality group with both resilient and overcontroller attributes and a confident personality group with both resilient and undercontroller attributes (we are grateful to one of the reviewers to point this out to us). We constructed a reserved personality group by selecting those adolescents who switched between the resilient and overcontroller types (n ¼ 92) and a confident personality group by selecting those adolescents who switched between the resilient and undercontroller types (n ¼ 138) over the three waves.…”
Section: Strategy Of Analysesmentioning
confidence: 99%
“…Četvrti tip ličnosti Barbaranelli naziva nepoželjnim, a u toj grupi su ispitanici sa visokim vrednostima na Neuroticizmu, a niskim na Savesnosti, Prijatnosti i Ekstraverziji. Sličnu grupu ispitanika izdvajaju i Schnabel i saradnici (Schnabel et al, 2002), u čijem istraži-vanju je izolovan skup "impulsivnih"u okviru hiperkontrolisanog tipa.Istraživanja koja sprovode Herzberg i Roth (Herzberg & Roth, 2006) i Roth i VonCollani (Roth & Von Collani, 2007) nude soluciju s pet tipova ličnosti. U prvom slučaju, osim rezilijentnog, hiperkontrolisanog i hipokontrolisanog, pominju se i samopouzdani tip ličnosti (visoki skorovi na Ekstraverziji i Otvorenosti, umereni na ostalim dimenzijama) i rezervisani tip ličnosti (niski Neuroticizam, Ekstraverzija i Otvorenost, a umereno visoke Prijatnost i Savesnost).…”
unclassified
“…U prvom slučaju, osim rezilijentnog, hiperkontrolisanog i hipokontrolisanog, pominju se i samopouzdani tip ličnosti (visoki skorovi na Ekstraverziji i Otvorenosti, umereni na ostalim dimenzijama) i rezervisani tip ličnosti (niski Neuroticizam, Ekstraverzija i Otvorenost, a umereno visoke Prijatnost i Savesnost). Ova solucija pokazala se stabilnom u opštoj i zatvorskoj populaciji (Herzberg & Roth, 2006). U drugom istraživanju, iako se ponovo rešenje s pet klastera pokazalo boljim, ono nije isto kao u prethodnom, a izdvajaju se rezervisani, nepoželjni, rezilijentni, hipokontrolisani i samopouzdani tipovi ličnosti.…”
unclassified